BUILDING ADMINISTRATIVE CAPACITY: TACKLING DOMESTIC VIOLENCE AMIDST THE COVID-19 PANDEMIC - Wiranti, Dyah Ayu (Fakultas Politik Pemerintahan, 2023)
The implementation of Covid-19 mitigation policies has hindered the effective functioning of public services. During the Covid-19 pandemic, domestic violence cases remained hidden due to victims' limited access to reporting channels, despite the government's efforts in establishing P2TP2A and SEJIWA psychological services. The persistently high incidence of domestic violence prompted Farazmand (2009) to advocate for increasing the state's administrative capacity to confront unforeseen challenges. This article examines Indonesia's approach to addressing domestic violence during the pandemic through Farazmand's Administrative Capacity Building recipe, utilizing a descriptive qualitative methodology with a literature study. The analysis reveals a pressing need for preventive services in Indonesia, such as social marketing and the implementation of artificial intelligence (AI) technology in creating applications that can proactively combat domestic violence, aligning with Farazmand's notion of